Influence of Thickness of Layers MoNС…/CrNy in Multilayer Coating and Nitriding on Structural and Mechanical Characteristics - V.O.В Stolboviy (Журнал нано- та електронної фізики)
In this paper, the processes of formation of multilayer MoNx/CrNy coatings on the nitrided surface of steel 12РҐ18Рќ10Рў are considered. The change in the concentration of nitrogen in the Mo, Cr, and in the depth of the steel is shown. The microhardness of the nitrated steel layer reaches 9В GPa, which increases adhesion properties with a multilayer coating. In multi-layer MoNx/CrNy coatings, nitrogen concentration is much higher in CrN than Mo2N.